Efectos de la educación intercultural en el desarrollo de competencias en estudiantes de secundaria de la Institución Educativa N° 6010189 Jesús de Praga, San Pablo Ramón Castilla 2022 - Mesia Mora, Lenther Wagner (2023)
The general objective of the research was: Determine the effect of Intercultural Education on the Development of Competencies in Secondary School Students of the Educational Institution No. 6010189 “Jesús de Praga” located in the district of San Pablo – Ramón Castilla province in the year 2022. The research was evaluative. Quasi-experimental research was used with pre and posttest with a single group. The population was made up of 77 students from Educational Institution No. 6010189 “Jesus of Prague”. From which a sample was drawn consisting of 43 Secondary Education students from Educational Institution No. 6010189 “Jesús de Praga” located in the district of San Pablo – Ramón Castilla province in the year 2022. The selection of the sample was extracted from of the sampling design for populations less than 1,500. The data collection instrument that was used was the pre- and post-test that had the purpose of studying the effect of Intercultural Education on the Development of Competence Builds Historical Interpretations in Secondary School Students of Educational Institution No. 6010189 “Jesus of Prague” before and after the application of Intercultural Education. The results show that there is a significant difference between the Development of the competence. Build historical interpretations by relating the results before and after the application of Intercultural Education, based on the Wilcoxon signed rank test statistic with a calculated Z value. = -4,700. Therefore, the research hypothesis is accepted: “Intercultural Education has an effect on the Development of Competence Builds historical interpretations in Secondary School students of the Educational Institution No. 6010189 “Jesus of Prague” located in the district of San Pablo – Ramón Castilla province in the year 2022.”